Wpływ sekurytyzacji na sytuację finansową banków - Półtorak, Bogusław (The impact of securitisation on the bank standing, 2006)
The bank system has been still changed in Poland. Its role in keeping potential of state in long term period has grown. Therefore stability of the bank sector is an important factor for economic condition of the financial system in Poland. Dynamic development of credit action is due to growing needs of private and public subjects as well as individual clients. In modem economies the role of banks has been transformed. They are more the originators of securitisation then the traditional deposit banks. One of the immediate priorities for banking supervision will be to monitor the practices of the banks in changing their lending rules and taking deposits. The New Basel Capital Accord will implement new rules of risk approach. What should change an evaluation of capital adequacy. Higher-risk activities will require adjusting financial innovation. Using of that innovation (e.g. synthetic securitisation) approved by banking supervision will decrease the cost of bank own capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 409-417